Pendekatan Governance dan Governability dalam Kebijakan Tata Kelola Lingkungan untuk Mewujudkan Keberlanjutan Lingkungan yang Efektif - Chamid Sutikno; Denok Kurniasih (Universitas 17 Agustus 1945, 2025)
Environmental issues have become one of the primary focal points with high priority at regional, national, and international levels. A comprehensive understanding, free from dichotomy, is crucial in formulating policies related to sustainable development that integrate the dimensions of nature, social space, and the environment. The environmental degradation currently being experienced is a serious problem that requires in-depth attention from all stakeholders. Therefore, strong commitment and strategic action from the government are necessary to formulate policies that address the challenges of environmental damage that continue to escalate. Indonesia, as a country in Asia, plays a vital role in controlling global climate change and environmental governance. The approaches of governance and governability in environmental policy emphasize the importance of building institutional networks and partnerships from various sectors, including government, society, and the private sector (multi-stakeholders). All actors involved must share a common vision on environmental policies and strive to integrate environmental issues across various sectors, such as economics, social affairs, and politics. These governance and governability approaches must be grounded in the principles of green government and green policy, which have already been established as part of the national development agenda. This approach also highlights the importance of principles that are long-term, relevant, stable, prudent, and self-reliant in responding to environmental governance and policy issues in Indonesia. By applying these principles, it is hoped that the policies implemented will be more effective and provide positive impacts for environmental sustainability. Therefore, collaboration between the government and all relevant sectors is crucial in creating policies that ensure the continued preservation of the environment for the welfare of future generations.